Identification of Co-Existing Mutations and Gene Expression Trends Associated With K13-Mediated Artemisinin Resistance in Plasmodium falciparum - Rawat, Mukul; Kanyal, Abhishek; Choubey, Deepak; Deshmukh, Bhagyashree; Malhotra, Rashim; Mamatharani, DV; Rao, Anjani Gopal; Karmodiya, Krishanpal (Frontiers in Genetics, 2022)
Plasmodium falciparum infects millions and kills thousands of people annually the world over. With the emergence of artemisinin and/or multidrug resistant strains of the pathogen it has become even more challenging to control and eliminate the disease. Multiomics studies of the parasite have started to provide a glimpse into the confounding genetics and mechanisms of artemisinin resistance and identified mutations in Kelch13 (K13) as a molecular marker of resistance. Over the years thousands of genomes and transcriptomes of artemisinin resistant/sensitive isolates have been documented supplementing the search for new genes/pathways to target artemisinin resistant isolates. This meta-analysis seeks to recap the genetic landscape and the transcriptional deregulation that demarcate artemisinin resistance in the field. In order to explore the genetic territory of artemisinin resistance, we use genomic SNP datasets from 2,517 isolates from 15 countries from the MalariaGEN Network (The Pf3K project, pilot data release 4, 2015) to dissect the prevalence, geographical distribution and co-existing patterns of genetic markers associated with/enabling artemisinin resistance. We have identified several mutations which co-exist with the established markers of artemisinin resistance. Interestingly, K13 resistant parasites harbor α-ß hydrolase and putative HECT-domain-containing protein genes with the maximum number of SNPs. We have also explored the multiple, publicly available transcriptomics datasets to identify genes from key biological pathways whose consistent deregulation may be contributing to the biology of resistant parasites. Surprisingly, glycolytic and pentose phosphate pathways were consistently downregulated in artemisinin-resistant parasites. Thus, this meta-analysis highlights the genetic and transcriptomics features of resistant parasites to propel further exploratory studies in the community to tackle artemisinin resistance.